Minor neurological dysfunction in children aged 5 to 7 - Galić, Maja; Mikov, Aleksandra; Sekulić, Slobodan; Kopitović, Aleksandar; Peričin Starčević, Ivana (Vojnosanitetski pregled, 2020)
Background/Aim. Assessment of minor neurological dysfunction (MND) provides information about a child's neurological condition which helps to identify the vulnerability of the child to the development of motor impairment, difficulties in learning or behavioral disorders. The aim of this study was to determine differences in the prevalence of MND in children from the general population with respect to age (5 and 6 years old) and sex. Methods. The examination was carried out in a preschool institution in the city of Novi Sad, Serbia. The total sample included 120 children divided into two groups according to age: 60 children aged 5 (group A) and 60 children aged 6 years (group B). The children were recruited at three randomly selected kindergartens and approximately equal sex representation, randomly selected as well. The testing was done by the Touwen's test, modified by Hadders-Algra. The results were classified into three groups: the absence of MND, presence of simple MND (presence of one or two domains of dysfunction) and the presence of complex MND (presence of at least three domains of dysfunction). Results. Sixty-seven children out of 120 (55.8%) had a normal neurological condition, while 53 (44.2%) showed MND [49 (40.8%) simple, and 4 (3.4%) complex]. MND occurred more frequently in the youngest age group than in the older children (57% vs. 32%; p = 0.01). MND was also more frequent in boys than in girls, but this difference was not statistically significant. Conclusion. Our results show the importance of testing children at preschool age in order to detect potential neurological vulnerability and timely begin with the appropriate therapy.
Keywords: neurological manifestations; risk; child; child, preschool; age factors; sex factors.